PERKEMBANGAN EKSPOR MINYAK KELAPA SAWIT (CRUDE PALM OIL) INDONESIA PERIODE 2008 – 2015 - Bryan Enhance Relity S. (CALYPTRA, 2018)
Palm oil is one of Indonesia's export commodities which is quite important as a producer of foreign exchange other than oil and gas. This study aims to analyze the development of crude palm oil (CPO) exports in 2008-2015. The research method used is qualitative research with descriptive model. Sources of data in this study using data both obtained from primary data and secondary data, is dat a obtained in the form so compiled by other parties directly related. The results show that, the development of the Indonesian crude palm oil industry shows a significant increase every year. In addition, the results of the research are also known problems in the export of crude palm oil that is the increase of export tax, the competition of CPO producers, the issue of global warming, black campaign, Pests and diseases. As well as, the development strategy that needs to be done is in the export competition that is, optimizing the plantation land, developing CPO production by utilizing technology, conducting human resources training, developing competitive strategy and developing promotion.